Post-vaccinated asymptomatic rotavirus infections: A community profile study of children in Surabaya, Indonesia - Emily Gunawan; Takako Utsumi; Rury M. Wahyuni; Zayyin Dinana; Subijanto M. Sudarmo; Ikuo Shoji; Soetjipto; Maria I. Lusida (Elsevier, 2019)
Background: Rotavirus gastroenteritis accounts for significant childhood morbidity and mortality worldwide. Vaccination using RotarixTM (GSK) and RotaTeq® (Merck) was introduced due to the tremendous disease burden. The possibility of asymptomatic infections following vaccinations was poorly understood. This study examined rotavirus cases in post-vaccinated children, their clinical manifestations and the genotypes of isolated strains. Methods: Stool samples of healthy, vaccinated children under 5 years of age in Surabaya were collected monthly for 1 year between January 2016 and February 2017. Episodes of gastroenteritis were reported, and samples were collected. Rotavirus was identified using multiplex reverse transcription Polymerase Chain Reaction (QIAGEN, Inc., Valencia, CA). Clinical manifestations were measured using the Vesikari score. The genotype was analyzed by Applied Biosystems (Foster, CA). Results: A total of 109 stool samples were collected from 30 subjects, of which 22 received Rotarix; 8 RotaTeq. Nine out of 109 samples were collected during diarrhea episodes of 8 subjects. Two asymptomatic rotavirus infections were identified by RT-PCR. The genotypes isolated were G1P[8] and G3P[8]. Conclusions: Asymptomatic rotavirus infections can occur in post-vaccinated children. Strains identified were homologous to serotypes eliciting gastroenteritis in unvaccinated children of the same community. Keywords: Rotavirus, Asymptomatic, Post-vaccination, Genotyping